Ametropía congénita progresiva en paciente masculino de 15 años. - Ponce Espinoza, David Javier (2022)
The present research work is about a 15-year-old male patient who presents a progressive congenital ametropia. This type of ametropia is very relevant, the professional optometrist must detect them at an early age, when ametropia is not treated in time it can cause more serious problems, loss of vision, amblyopia, the eye gets used to not seeing well. When children exhibit symptoms such as frowning, straining to see far or near, headaches, and squinting, these are signs that they have a visual problem. The objective of this study is to identify the cause of visual acuity loss in both eyes. The patient underwent the respective tests such as retinoscopy, auto refractometer, Donders test, biomicroscopy, among others. The patient presented headache, burning, stinging and redness of the eyes when performing tasks and not using his lenses. Once the tests have been carried out, it is determined that the patient has myopia and congenital astigmatism of a progressive nature, this is the consequence of not using any type of visual aid at an early age and the excessive use of electronic equipment have accelerated the increase in measurements.